Latin American Christians Living in the Basque Country (Spain): What Remains and What Changes - Rodríguez, Lidia (Religions, 2020)
The research we will present is based on interviews conducted with the Latin American immigrant population and the indigenous population of the Basque Autonomous Community (BAC hereafter). We seek to identify religious features tracing similarities and differences between three populations: First, the native community of the BAC, second, Latin American immigrants living in the BAC, and third, Latin Americans in their home countries. In the latter case, we based on the research carried out by Gustavo Morello’s team. Analysis of the data obtained so far allows us to compare across two different processes in the Christian religion: On the one hand, the religious experience of Latin Americans in their countries of origin and the religious experience of Latin American immigrants in the BAC; on the other hand, between the latter community and the native population. This paper highlights conclusions referring: (1) The similarities in two significant processes, i.e., religious pluralism and religious autonomy; (2) the differences on religious hybridization, public presence and the use of religious artefacts. In short, it is a contribution to a better understanding of the effects produced on religious experiences in a context marked by secularization and religious pluralism.